PERAN PARTAI POLITIK DALAM PENDIDIKAN POLITIK GENERASI MUDA DAN IMPLIKASINYA TERHADAP KETAHANAN POLITIK WILAYAH (Studi Di DPD II Partai Golongan Karya Kota Malang Jawa Timur Tahun 2009 - 2014) - Saputro, Yulianto Dwi (Jurnal Ketahanan Nasional, 2015)
A political party was an important element in democratic countries. One of the functions of the establishment of political parties as political institutions that were responsible for providing political education to the cadres of political parties as well as to the wider community. In a democratic political system political party of choice as a means to realized the ideals of the nation and the state. Political education was an effort to realized the Indonesian democracy healthy and quality. This study aimed to discussed the role of political parties in the political education of the younger generation and its implications for political resilience in the study area with the second DPD Golkar Party Malang East Java. The method in this research was descriptive qualitative, which described the complex social phenomena occured in society. The research process was done by selecting informants who were deemed eligible research with purposive sampling method. In this case the Golkar Party offi cials Malang. The technique of research by conducting in-depth interviews, observation, literature study and documentation. Then analyzed with three grooves activities that occurred simultaneously, namely data reduction, data presentation, drawing conclusions or verifi cation The results showed that the role of political parties in providing the cadres and political education to the public remains low. Methods and materials for political education conducted by the political parties were still very conceptual and less applicable. Evaluation methods in the provision of political education was not operating effectively, so that the role of political parties in providing awareness to the community about the rights and obligations as citizens to be low. oreover, the resulting low level of quality cadres of political parties in encouraging the improvement of peopleâs lives. Implications of the role of political parties in the political education of the younger generation of political resilience of region adversely affected the political participation of society and the low level of public participation in public policy-making and oversight.Keywords: Political Parties, Political Education, Youth Generation, Political Resilience of Region.